AKSES BERBEDA, MASA DEPAN BERBEDA: PENDIDIKAN DI WILAYAH RURAL VS URBAN - Dewi Saputri, Andi; Rahman, Abdul; Nurhaedah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational inequality between rural and urban areas remains a major challenge in achieving educational equality in Indonesia. Differences in access to educational infrastructure, the quality of teaching staff, digital technology, and socioeconomic conditions lead to disparities in the quality of learning and educational opportunities for students. This study aims to systematically examine the various factors influencing the educational gap between rural and urban areas, its impact on students' futures, and strategies that can be implemented to reduce this inequality. The study used the Systematic Literature Review (SLR) method with the PRISMA approach. Data were obtained from national and international scientific articles published during the 2020-2026 period and sourced from the Google Scholar, Scopus, ScienceDirect, ERIC, DOAJ, and Garuda databases. From the results of the literature identification and selection process, 15 articles were obtained that met the inclusion criteria for analysis using a thematic synthesis approach. The results show that schools in urban areas have better access to educational facilities and infrastructure, digital technology, and qualified teaching staff compared to schools in rural areas. This gap impacts academic achievement, access to further education, and career development opportunities for students. Furthermore, the digital divide and the unequal distribution of teachers are dominant factors widening educational inequality. Therefore, policies focused on equitable distribution of educational infrastructure, strengthening school digitalization, and a more equitable distribution of teaching staff are needed to achieve inclusive and sustainable education.